(untitled) (Revista Espinhaço, 2021)
This paper presents the exhibition (Re)visiting the landscape from Espinhaço Range Biosphere Reserve (RBSE) with Martius and Spix (1818-2018), in Diamantina between 2018/2019 as a teaching practice in a non-formal space. e exhibition consisted of banners with information on the landscapes described by the naturalists Spix and Martius by the RBSE in 1818 and sensory practices that immersed visitors in the 19th century. e themes as nature conservation, environmental degradation, geodiversity, and regional biodiversity are linked to the Common National Curriculum Base in Geography, Science, History and Human Science areas. About 2,300 people visited the exhibition, with 450 students from basic education and 180 from higher education. We develop practices such as paintings, paper folding and planting seeds of native Cerrado species described in Flora Brasiliensis at the end of visits. ese ludic activities developed with enthusiasm by visiting teachers and students.